Можливості створення машин сільськогосподарського призначення з електротрансмісією та комбінованими системами енергоживлення - Шидловський, А.К.; Павлов, В.Б.; Третяк, М.В. (Технічна електродинаміка, 2012)
Various aspects of improving the efficiency of agricultural machinery, both in terms of energy management and in the direction of power distribution to assemblies. It is noted that the use of electric transmission has a number of positive results in the operation of agricultural machinery as part of ergonomics, and on ways to reduce fuel consumption. At the same time it is shown that the use of combined systems of energy supply can improve the efficiency of agricultural machinery and reduce operating energy costs.